Penyembuhan luka Ulkus Diabetik dengan Dressing Madu Murni: Literature Review - Pujiastuti, Nurul - (Journal of Local Therapy, 2023)
Poor peripheral circulation in patients with diabetes mellitus causes wounds to be difficult to heal. Therefore, patients with diabetes mellitus with diabetic ulcers require wound care to reduce the risk of amputation. One alternative material that can be used for wound care is the topical application of pure honey. The purpose of the study was to determine the effect of honey dressing on the healing process of diabetic ulcers through a literature review. The databases used include PubMed, ScienceDirect, Google Scholar, and Garuda. Keywords using (((honey) OR honey dressing) AND wound healing) AND diabetic ulcer) OR diabetic foot ulcer. The library sources used are from 2010-2020. The search results obtained 9,507 articles. Furthermore, articles were selected based on inclusion and exclusion criteria, obtained 11 articles. The assessment of articles uses a checklist on the JBI (Joanna Briggs Institute) assessment list. Eleven articles that met the assessment criteria were then analyzed one by one. The results showed that eleven articles showed the effect of giving honey dressing on the healing process of diabetic ulcers. A total of 3 articles showed wound healing based on changes in score, 2 articles based on changes in grade, 5 articles based on changes in wound characteristics, and 2 articles based on healing time. Of the eleven journals analyzed, honey dressing on diabetic ulcers were most effectively used in wound Grade I and II (Wagner Classification) ulcer patients who received drug therapy with a GDS <200 mg/dL and received daily wound care for 1 month. Healthcare professionals may consider using honey dressings for the treatment of diabetic ulcers. In addition to a more affordable price, honey has good benefits for wound healing. Further research is needed on the type of honey that is more effective as an ingredient in wound care.